ChemInform Abstract: Synthesis, Crystal Structure, and Physical Properties of a New Boride Ga2Ni21B20 with a Modified Zn2Ni21B20‐Type Structure. Issue 29 (29th June 2016) - Zheng, Qiang; Gumeniuk, Roman; Schnelle, Walter; Prots, Yurii; Burkhardt, Ulrich; Leithe‐Jasper, Andreas
Abstract: Ga2 Ni21 B20 is prepared by both arc melting of the elements (10 wt% excess Ga) and by arc melting of B and Ni foil followed by reaction with Ga (Al2 O3 crucible, ≈1300 °C).